Remarkably enhanced photocatalytic activity by sulfur-doped titanium dioxide in nanohybrids with carbon nanotubes. (December 2016) - Khang, Nguyen Cao; Van, Duong Quoc; Thuy, Nguyen Minh; Minh, Nguyen Van; Minh, Phan Ngoc
Abstract: TiO2 doped S nanohybrids with carbon nanotubes (CNTs) were synthesized with CNTs, thiourea and TiO2 nanoparticles. The result indicated that the TiO2 nanoparticles with about 8 nm in size are attached on the sidewall of CNTs. The nanohybrids material can absorb at longer wavelength and the absorption even covers the whole range of visible region than that only TiO2 nanoparticles. Application of the catalysts to photocatalytic degradation of methylene blue (MB) was tested under visible light irradiation. The result suggests that a high MB degradation activity of S-TiO2 /CNTs due to a reduce band gap of TiO2 when S is doped, and the decrease in the possibility of electron–hole recombination by CNTs. In addition, the density functional-theory (DFT) calculations of the electronic band structures and density of states (DOS) to understand the bonding states between TiO2 and CNTs, proved that the TiO2 /CNTs system is stable. Graphical abstract: Highlights: The nanohybrids S-doped TiO2 /CNTs materials were synthesized by hydrolysis method. The percent of dyes decomposed highest at the sample with [TiO2 ]/[thiourea]=1/4. ΔEads are −1.95 eV suggest that the adsorption processes are spontaneous. High photocatalytic due to bandgap reduction by S-doped, lower electron-hole recombination by CNTs.